1986
DOI: 10.1007/bf00166695
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of polypropylene in the human eye: A sem-study

Abstract: A polypropylene surgical suture, which had served as fixation suture for an IOL for a period of 6.5 years, was removed from the eye of a Dutch patient because it had broken at one end and thus formed a potential risk for a corneal touch syndrome. After careful rinsing in 50% ethanol, to remove adhering debris, it was prepared for SEM. A virgin piece of polypropylene material from a surgical package underwent the same preparative procedure. The fixation suture showed cracks perpendicular to the longitudinal axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Although there were no cases of suture degradation that caused IOL instability in our study, the durability of the Prolene 10-0 suture can be another limitation of our study. 23,40,41 Recent studies have shown that breakage of Prolene 10-0 suture occurred in 6.1% after a mean of 4.9 years. 42 To overcome this concern, using 9-0 Prolene instead of 10-0 for transscleral fixation could be an option.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were no cases of suture degradation that caused IOL instability in our study, the durability of the Prolene 10-0 suture can be another limitation of our study. 23,40,41 Recent studies have shown that breakage of Prolene 10-0 suture occurred in 6.1% after a mean of 4.9 years. 42 To overcome this concern, using 9-0 Prolene instead of 10-0 for transscleral fixation could be an option.…”
Section: Discussionmentioning
confidence: 99%
“…Polypropylene generally has a long life, but some studies have demonstrated suture biodegradation and noted that polypropylene does not provide permanent IOL fixation. [12][13][14] Based on recent concerns about the durability of this suture, there has been increasing use of 9-0 polypropylene for transscleral fixation of PC IOLs. 12,15 To date, we have seen no signs of degradation; thus, this procedure may contribute to less tilt and decentration over the long term.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of oxygen in addition to Release of cytotoxic chemicals extreme temperature can also give rise to thermal oxidation. One of the earliest looks into PP degradation within the human body was performed by Jongebloed et al who removed a broken PP suture 6.5 years postimplantation from the human eye and compared it to a pristine suture of the same kind [77]. Using scanning electron microscopy (SEM), the suture showed cracks perpendicular to the axis of the suture, with significant breakage and missing fragments.…”
Section: Degradation Of Pp Meshmentioning
confidence: 99%